Athletes' satisfaction as mediator of transformational leadership behaviors of coaches and football players' sport commitment relationship - Saybani, H.; Yusof, A.; Soon, C.; Hassan, Aminuddin; Zardoshtian, S. (IDOSI Publications, 2013)
The purpose of this study was to investigate the mediation role of athlete satisfaction on the relationship between transformational leadership style of Iranian high schools’ coaches and sport commitment of Iranian high schools’ football players and also to develop a coaching model. The survey design, correlational study and inferential statistics were applied in this research. The Structural Equation Modeling (SEM) was applied as a strong procedure to analyze the data and develop the models. Population of this study was 558 football players (15-20 years). 280 high schools’ football players were selected to participate in this study by using the simple random sampling procedure. Instruments of the study were MLQ (Avolio and Bass, 1995), SCMS (Scanlan,et al., 1993) and ASQ ( Riemer and Chelladurai, 1998). Moreover, SEM and ANOVA (Analysis of Variance) applied for testing hypotheses of the study. The results of the study indicated that there is a positive and significant relationship between transformational leadership style of coaches and athlete’s satisfaction of football players. In addition, athlete satisfaction significantly mediated the relationship between transformational leadership style of coaches and sport commitment of football players. All fit indices of the measurement and mediation models were acceptable. There these models were fit the data of the current study. Findings of this study revealed that transformational coaches with increasing satisfaction of football players would increase the sport commitment of football players.